2019
DOI: 10.18805/ag.a-5161
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of impact of anaerobic condition on the aflatoxin production in Aspergillus parasiticus Speare

Abstract: Aflatoxins are the natural carcinogens that are the best characterized as fungal secondary metabolites. The producers that are responsible for aflatoxin biosynthesis are strongly associated in toxic contamination of essential agricultural products. Aspergillus parasiticus is an exclusive fungus that participates in causing hepatic problems in humans and cattle. These mycotoxins are greatly influenced by abiotic stresses. The fungal growth, proliferation and its toxigenicity are highly i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…In them, neoeriocitrin and blasticidin-S are the most efficient compounds, showing good docking results in many possible positions within the target protein. A more detailed structural view of the relationship can be made using hydrophobic interactions and hydrogen bonding interactions [ 15 ]. It is important to note that the blasticidin s that received the highest docking score appeared to block the targeted domain more effectively than any of the others.…”
Section: Resultsmentioning
confidence: 99%
“…In them, neoeriocitrin and blasticidin-S are the most efficient compounds, showing good docking results in many possible positions within the target protein. A more detailed structural view of the relationship can be made using hydrophobic interactions and hydrogen bonding interactions [ 15 ]. It is important to note that the blasticidin s that received the highest docking score appeared to block the targeted domain more effectively than any of the others.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the lack of an immediately available standard diagnostic test, the high mortality rate associated with IPA poses a significant problem. [33][34][35] Chen and his team initially worked on the inflammation due to IPA. They injected cyclophosphamide intraperitoneally into mice to create a neutropenic model and found that the mice's neutrophil count remained below 100/mm3 throughout the study.…”
Section: The Mirnas Involved In Inflammation During Aspergillus Infec...mentioning
confidence: 99%
“…The flow rate was kept at 1ml/min throughout the analysis and the acquisition was performed at 25ºC for 20 minutes. [23] Anti P. acne activity of glabridin The antimicrobial activity of glabridin against P. acne (ATCC 6919) was determined by well diffusion assay. The assay was performed on Muller Hinton Agar (MHA) in anaerobic condition.…”
Section: Hplc Analysismentioning
confidence: 99%